2022
DOI: 10.3390/biom12111691
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Dopaminergic and Glutamatergic Systems in the Valproic Acid Mouse Model of Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a progressive neurodevelopmental disorder mainly characterized by deficits in social communication and stereotyped behaviors and interests. Here, we aimed to investigate the state of several key players in the dopamine and glutamate neurotransmission systems in the valproic acid (VPA) animal model that was administered to E12.5 pregnant females as a single dose (450 mg/kg). We report no alterations in the number of mesencephalic dopamine neurons or in protein levels of tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…At variance with our findings (Ádám et al, 2020, present study), no difference was found in either the abundance of DAergic neurons of SN or VTA, or the expression of TH in CPu or NAc, in mice prenatally exposed to VPA (Maisterrena et al, 2022). The apparent controversy may be due to the different age of animals (P7 in our study, and P21 in the cited study), and to methodological differences in preparing samples for WB.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…At variance with our findings (Ádám et al, 2020, present study), no difference was found in either the abundance of DAergic neurons of SN or VTA, or the expression of TH in CPu or NAc, in mice prenatally exposed to VPA (Maisterrena et al, 2022). The apparent controversy may be due to the different age of animals (P7 in our study, and P21 in the cited study), and to methodological differences in preparing samples for WB.…”
Section: Discussioncontrasting
confidence: 92%
“…The cited authors used whole lysates for WB, whereas we prepared crude synaptosome fraction from the primary lysate, which, in our opinion, represents synaptic and membrane-bound TH more specifically. Interestingly, Maisterrena et al (2022) reported an upregulation of DA receptors, indicating an underlying reduction of ligand (DA), which may have had occurred (unnoticed, in that case) prior to the age (P21) at which their samples for immunoblotting were collected. Similarly, upregulation of first D2 (at P35-40), then D1 receptors (at P90-95) was observed in the NAc of rats born to VPA-exposed mothers, (with no data on P7 animals), by Schiavi et al (2019), together with characteristic behavioral and electrophysiological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Gene variants associated with dopaminergic markers and receptors have been identified in ASD ( De Krom et al, 2009 ; Staal et al, 2012 ; Gangi et al, 2016 ; Mariggiò et al, 2021 ). Several ASD animal models show increased gene expression of dopamine D2 receptors in iMSNs ( Maisterrena et al, 2022 Chhabra et al, 2023 ; reviewed in Gandhi and Lee, 2021 ). Increased striatal levels of dopamine D2 receptors was documented in Rett syndrome ( Chiron et al, 1993 ) and more recently, increased striatal D2 receptor gene expression has been reported in ASD post-mortem brains ( Brandenburg et al, 2020 ).…”
Section: Dopamine Control Of Cortico-striatal Inputs and Asd Behavior...mentioning
confidence: 99%
“…In mice, knock-down of neuroligin 2, another ASD-associated gene, results in a reduction in the density of dopaminergic synapses and an increase in the number of GABAergic synapses onto MSN ( Uchigashima et al, 2016 ). In the valproic model of ASD, dopamine levels are decreased and dopamine turnover is increased in the dorsal striatum while dopamine receptor expression is increased in the nucleus accumbens ( Maisterrena et al, 2022 ). These convergent findings suggest that altered dopaminergic modulation of corticostriatal inputs onto MSNs is a key pathophysiological feature of ASD.…”
Section: Dopamine Control Of Cortico-striatal Inputs and Asd Behavior...mentioning
confidence: 99%
“…Accordingly, several animal models of ASD, including both pharmacological models and genetic models generated by mutations in genes found in patients with ASD, show glutamatergic alterations. Excitotoxicity, altered glutamate homeostasis, and receptor subunit expression and regulation were reported in the brain of a valproic acid model, one of the most widely used animal models of ASD [ 30 , 31 , 32 , 33 ]. Similarly, Shank mutant mice clearly exhibit glutamatergic impairments [ 34 , 35 , 36 , 37 ].…”
Section: Involvement Of Glutamate Excitotoxicity In Autism Spectrum D...mentioning
confidence: 99%